Acute and Subchronic Toxicity Assessment of 70% Ethanol Extract of Gendarusa Leaves In Vivo - Luthfiatu Kanina; Mabluhatus Solehah; Hani Plumeriastuti; Retno Widyowati; Bambang Prajogo Eko Wardoyo (JURNAL FARMASI DAN ILMU KEFARMASIAN INDONESIA, 2022)
Background: Justicia gendarussa Burm. f., has been used traditionally in Indonesia for antifertility. Nowadays, a capsule containing 70% ethanol extract of J. gendarussa leaves has been studied for safety. Objective: This study aimed to determine the acute and sub-chronic toxicity of 70% ethanol extract of J. gendarussa leaves in vivo. Methods: In the acute toxicity study, a single dose of 2,000"‰mg/Kg BW was orally administered to mice (n = 10), which were monitored for 24"‰days. For the subchronic toxicity study, rats were randomly divided into four groups (n = 10). The control group received distilled water, while the treatment groups received a repeated dose of 40, 200, and 1,000 mg/Kg BW orally for 90 days. Blood samples were collected for hematological and biochemical evaluations. Gross pathology and histopathology of liver and kidneys were assessed. Results: No mortality and non-observed adverse effect level (NOAEL) were observed in the acute toxicity study. The hematological analysis did not show significant differences in the subchronic toxicity study. The SPGT, SGOT, and creatinine values showed no change in groups 2 and 4, but the level of SGPT increased in groups 3. The increasing level of BUN was observed in all treated groups. Abnormalities or histopathological changes were observed in the liver and kidney in groups 3 and 4. Conclusions: Using 70% ethanol extract of J. gendarussa leaves at a therapeutic dose is safer, but it needs attention at a higher dose.